2010
DOI: 10.4278/ajhp.080603-quan-77
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviors of Employed and Insured Adults in the United States, 2004-2005

Abstract: Working insured adults are not meeting recommendations for health behaviors. Significant disparities in health behaviors related to socioeconomic status exist among this group. Employers and insurers should consider these poor health behaviors and disparities when designing insurance benefits addressing clinical preventive services utilization and workplace health promotion programs addressing lifestyle-related behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 30 publications
3
29
1
1
Order By: Relevance
“…Previous studies also find that the most common types of health-related behaviors are gender-specific, which is of interest for health promotion activities. 9,10,16 Although, our results regarding the socioeconomic determinants of daily smoking are compatible with previous studies, 4,9-15 we did not capture all associations found in previous studies for alcohol consumption. 10,17 This may to a certain extent be because of the variation in the way drinking behavior is measured and reported in different studies.…”
Section: Indicators Of Health-related Behaviorssupporting
confidence: 59%
See 2 more Smart Citations
“…Previous studies also find that the most common types of health-related behaviors are gender-specific, which is of interest for health promotion activities. 9,10,16 Although, our results regarding the socioeconomic determinants of daily smoking are compatible with previous studies, 4,9-15 we did not capture all associations found in previous studies for alcohol consumption. 10,17 This may to a certain extent be because of the variation in the way drinking behavior is measured and reported in different studies.…”
Section: Indicators Of Health-related Behaviorssupporting
confidence: 59%
“…9,10,16 Although, our results regarding the socioeconomic determinants of daily smoking are compatible with previous studies, 4,9-15 we did not capture all associations found in previous studies for alcohol consumption. 10,17 This may to a certain extent be because of the variation in the way drinking behavior is measured and reported in different studies. 11 It can also be explained by the fact that we use a wider range of factors which might pick up the effect of other socioeconomic variables.…”
Section: Indicators Of Health-related Behaviorssupporting
confidence: 59%
See 1 more Smart Citation
“…Even among insured adults, influenza vaccination represented the least frequently received preventative health service among routine recommended services (26%) during a 2-year study period. 18 Second, lack of insurance coverage for vaccine-eligible adults and potential loss of income (because of the need to take time from work for preventive care) add to the challenges. Third, many healthy adults are unaware of the continuing need for immunization and the risks to themselves or others when their immunizations are not current.…”
Section: Barriers To Immunization Of Adultsmentioning
confidence: 99%
“…17 Another study conducted in [2004][2005] reported that 74% of insured adults did not receive influenza vaccine. 18 With evidence to support the benefits of immunization of parents and other close family contacts for the protection of children, several barriers to adult immunization remain. First, there are patient factors, such as a reluctance of healthy adults to seek preventive health care.…”
Section: Barriers To Immunization Of Adultsmentioning
confidence: 99%